All‐Cause and Cause‐Specific Mortality Trends of End‐Stage Renal Disease Due to Lupus Nephritis From 1995 to 2014. Issue 3 (9th January 2019) - Jorge, April; Wallace, Zachary S.; Zhang, Yuqing; Lu, Na; Costenbader, Karen H.; Choi, Hyon K.
Abstract : Objective: A prior study showed that premature mortality among patients with end‐stage renal disease (ESRD) due to lupus nephritis (LN) persisted in the US between 1995 and 2006. The present study was undertaken to extend this analysis through 2014 to examine more recent trends, including key cause‐specific mortality trends. Methods: Using the national registry of patients with ESRD, we identified all patients with incident ESRD due to LN between January 1, 1995 and December 31, 2014, divided into four 5‐year cohorts of ESRD onset by calendar year (1995–1999, 2000–2004, 2005–2009, 2010–2014). We assessed mortality within each cohort. Temporal trends in all‐cause mortality and cause‐specific mortality were examined, adjusting for covariates. Results: We identified 20, 974 individuals with incident ESRD due to LN from 1995 through 2014. The mortality rate per 100 patient‐years declined from 11.1 (95% confidence interval [95% CI] 10.4–11.8) in 1995–1999 to 6.7 (95% CI 6.2–7.2) in 2010–2014 ( P for trend < 0.01). Adjusted mortality hazard ratios in 2010–2014, compared with 1995–1999, were 0.68 (95% CI 0.58–0.78) for white patients, 0.67 (95% CI 0.57–0.78) for African American patients, and 0.51 (95% CI 0.38–0.69) for Hispanic patients. Deaths from cardiovascular disease (CVD) and infection declined by 44% and 63%, respectively, from 1995–1999 to 2010–2014 ( P for trend < 0.01 for both). Conclusion: In the more recent years of the period 1995–2014, there was a considerable reduction in all‐cause mortality among white, African American, and Hispanic patients, with reduced risk of death from CVD and infection. Collectively, these trends provide an important benchmark of improving care in this high‐risk population.